Безумная кепка Мономаха - Донцова Дарья Аркадьевна (Иронический детектив, 2006)
Экземпляры: ф16 (20171110) / Инвентарный номер: 54991 / Цена: 15/00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6